Application of Time-Variable Gravity to Groundwater Storage Fluctuations in Saudi Arabia - Mohamed, Ahmed; Abdelrahman, Kamal; Abdelrady, Ahmed (Frontiers in Earth Science, 2022)
In the Middle East, water shortage is becoming more and more serious due to the development of agriculture and industry and the increase in population. Saudi Arabia is one of the most water-consuming countries in the Middle East, and urgent measures are needed. Therefore, we integrated data from Gravity Recovery and Climate Experiment (GRACE), and other relevant data to estimate changes in groundwater storage in Saudi Arabia. The findings are as follows: 1) Average annual precipitation (AAP) was calculated to be 76.4, 90, and 72 mm for the entire period, Period I (April 2002 to March 2006) and Period II (April 2006 to July 2016), respectively. 2) The average TWS variation was estimated to be −7.94 ± 0.22, −1.39 ± 1.35, and −8.38 ± 0.34 mm/yr for the entire period, Period I and Period II, respectively. 3) The average groundwater storage was estimated to be +1.56 ± 1.35 mm/yr during Period I. 4) The higher average groundwater depletion rate was calculated to be −6.05 ± 0.34 mm/yr during Period II. 5) Both soil texture and surface streams in the study area promote lateral flow and carry surface water to the Arabian Gulf and the Red Sea. 6) During Period II, average annual recharge rates were estimated to be +9.48 ± 2.37 and +4.20 ± 0.15 km3 for Saudi Arabia and the Saq aquifer, respectively. 7) This integrated approach is an informative and cost-effective technique to assess the variability of groundwater resources in large areas more efficiently.